Coexpression of GM-CSF and antigen in DNA prime-adenoviral vector boost immunization enhances polyfunctional CD8+ T cell responses, whereas expression of GM-CSF antigen fusion protein induces autoimmunity - Tenbusch, Matthias (BioMed Central, 2008)
BACKGROUND: Granulocyte-macrophage colony-stimulating factor (GM-CSF) has shown promising results as a cytokine adjuvant for antiviral vaccines and in various models of tumor gene therapy. To explore whether the targeting of antigens to GM-CSF receptors on antigen-presenting cells enhances antigen-specific CD8 T-cell responses, fusion proteins of GM-CSF and ovalbumin (OVA) were expressed by DNA and adenoviral vector vaccines. In addition, bicistronic vectors allowing independent expression of the antigen and the cytokine were tested in parallel. RESULTS: In vitro, the GM-CSF ovalbumin fusion protein (GM-OVA) led to the better stimulation of OVA-specific CD8+ T cells by antigen-presenting cells than OVA and GM-CSF given as two separate proteins. However, prime-boost immunizations of mice with DNA and adenoviral vector vaccines encoding GM-OVA suppressed CD8+ T-cell responses to OVA. OVA-specific IgG2a antibody levels were also reduced, while the IgG1 antibody response was enhanced. Suppression of CD8+ T cell responses by GM-OVA vaccines was associated with the induction of neutralizing antibodies to GM-CSF. In contrast, the coexpression of GM-CSF and antigens in DNA prime adenoviral boost immunizations led to a striking expansion of polyfunctional OVA-specific CD8+ T cells without the induction of autoantibodies. CONCLUSION: The induction of autoantibodies suggests a general note of caution regarding the use of highly immunogenic viral vector vaccines encoding fusion proteins between antigens and host proteins. In contrast, the expansion of polyfunctional OVA-specific CD8+ T cells after immunizations with bicistronic vectors further support a potential application of GM-CSF as an adjuvant for heterologous prime-boost regimens with genetic vaccines. Since DNA prime adenoviral vector boost regimenes are presently considered as one of the most efficient ways to induce CD8+ T cell responses in mice, non-human primates and humans, further enhancement of this response by GM-CSF is a striking observation.